Present culture status of the endangered snakehead, Channa striatus (Bloch, 1793) - Muntaziana, M. P. A.; Sarker, S. M. Nurul Amin Harmuj Ali; Rahman, Md. Aminur; Abd Rahim, Abdullah; Marimuthu, Kasi (Academic Journals, 2013)
Snakehead (Channa striatus) belonging to the Channidae family is an indigenous freshwater fish of Malaysia that has carnivorous behavior. C. striatus command high prices since it has a strong demand and are sold alive. It is a commercially important species in Thailand, Philippines, Cambodia and Vietnam. Increased human activities destroyed the feeding and breeding grounds of this species, leading to decline in wild catches. C. striatus is considered as an endangered fish in Bangladesh. The research of C. striatus provides an account of current knowledge, especially on reproduction, culture and nutritional requirement of snakehead. The problems encountered in snakehead culture are discussed and suggestions made to overcome the problems are highlighted.